Both Disease Activity and HLA–B27 Status Are Associated With Gut Microbiome Dysbiosis in Spondyloarthritis Patients. Issue 1 (19th November 2022) - Berland, Magali; Meslier, Victoria; Berreira Ibraim, Samar; Le Chatelier, Emmanuelle; Pons, Nicolas; Maziers, Nicolas; Thirion, Florence; Gauthier, Franck; Plaza Oñate, Florian; Furet, Jean‐Pierre; Leboime, Ariane; Said‐Nahal, Roula; et al.
Abstract : Objective: Gut microbiome dysbiosis has previously been reported in spondyloarthritis (SpA) patients and could be critically involved in the pathogenesis of this disorder. The objectives of this study were to further characterize the microbiota structure in SpA patients and to investigate the relationship between dysbiosis and disease activity in light of the putative influence of the genetic background. Methods: Shotgun sequencing was performed on fecal DNA isolated from stool samples from 2 groups of adult volunteers: SpA patients (n = 102) and healthy controls (n = 63). A subset of the healthy controls comprised the age‐matched siblings of patients whose HLA–B27 status was known. Changes in gut microbiota composition were assessed based on species diversity, enterotypes, and taxonomic and functional differences. Results: Dysbiosis was confirmed in SpA patients as compared to healthy controls. The restriction of microbiota diversity was detected in patients with the most active disease, and the abundance of several bacterial species was correlated with Bath Ankylosing Spondylitis Disease Activity Index score. Among healthy controls, significant differences in microbiota composition were also detected between the HLA–B27–positive and the HLA–B27–negative siblings of SpA patients. We highlighted a decreased abundance of several species of bacteria in SpA patients, especially those bacteria belonging to the Clostridiales order. Among the few species of bacteria showing increased abundance, Ruminococcus gnavus was one of the top differentiating species. Conclusion: These findings reveal that genetic background and level of disease activity are likely to influence the composition of the gut microbiota of patients with SpA. It may be appropriate for further research on chronic arthritis to focus on these key parameters.